The Usefulness of the TAPSE/sPAP Ratio for Predicting Survival in Medically Treated Chronic Thromboembolic Pulmonary Hypertension - Çolak, Ayşe; Kumral, Zeynep; Kış, Mehmet; Şentürk, Bihter; Sezgin, Dilek; Ömeroğlu Şimşek, Gökçen; Sevinç, Can; Akdeniz, Bahri (Turk Kardiyoloji Dernegi arsivi : Turk Kardiyoloji Derneginin yayin organidir, 2023)
The ventriculoarterial uncoupling has been linked with unfavorable results as measured noninvasively by tricuspid annular plane systolic excursion divided by systolic pulmonary artery pressure (TAPSE/sPAP). However, its prognostic importance in chronic thromboembolic pulmonary hypertension (CTEPH) is limited. Thus, we determine the effect of the TAPSE/sPAP ratio on outcomes and predictors of all-cause mortality in these patients.OBJECTIVEThe ventriculoarterial uncoupling has been linked with unfavorable results as measured noninvasively by tricuspid annular plane systolic excursion divided by systolic pulmonary artery pressure (TAPSE/sPAP). However, its prognostic importance in chronic thromboembolic pulmonary hypertension (CTEPH) is limited. Thus, we determine the effect of the TAPSE/sPAP ratio on outcomes and predictors of all-cause mortality in these patients.We analyzed 56 subjects with medically treated CTEPH. Two-dimensional echocardiographic examination and right heart catheterization findings were recorded from the hospital database. Baseline New York Heart Association functional class (NYHA-FC), 6-min walk distance (6MWD), and brain natriuretic peptide (BNP) test results were recorded.METHODSWe analyzed 56 subjects with medically treated CTEPH. Two-dimensional echocardiographic examination and right heart catheterization findings were recorded from the hospital database. Baseline New York Heart Association functional class (NYHA-FC), 6-min walk distance (6MWD), and brain natriuretic peptide (BNP) test results were recorded.The median age was 65.5 years. Over a median follow-up time of 27 months, 29 (51.8%) patients died. BNP values were higher (P = 0.008), 6MWD values were lower (P = 0.004), and NHYA-FC (P = 0.0001) was worse in the non-survivor group. TAPSE (P = 0.0001) and TAPSE/sPAP ratio (P = 0.001) were significantly lower and pulmonary vascular resistance (PVR) was higher in the non-survivor group (P = 0.03). The best cut-off value for the TAPSE/sPAP ratio for predicting mortality was 0.20 mm/mmHg and the survival rates were significantly lower in the TAPSE/sPAP ratio ≤0.20 group (log-rank P = 0.012). 6MWD (P = 0.005), NHYA-FC III-IV (P = 0.0001), TAPSE/sPAP ratio ≤0.20 (P = 0.017), PVR (P = 0.008), and TAPSE/sPAP ratio ≤0.20 combined with NYHA-FC III-IV (P = 0.0001) were significant determinants and TAPSE/sPAP ratio ≤0.20 combined with NYHA-FC III-IV was the only independent predictor of mortality (P = 0.003).RESULTSThe median age was 65.5 years. Over a median follow-up time of 27 months, 29 (51.8%) patients died. BNP values were higher (P = 0.008), 6MWD values were lower (P = 0.004), and NHYA-FC (P = 0.0001) was worse in the non-survivor group. TAPSE (P = 0.0001) and TAPSE/sPAP ratio (P = 0.001) were significantly lower and pulmonary vascular resistance (PVR) was higher in the non-survivor group (P = 0.03). The best cut-off value for the TAPSE/sPAP ratio for predicting mortality was 0.20 mm/mmHg and the survival rates were significantly lower in the TAPSE/sPAP ratio ≤0.20 group (log-rank P = 0.012). 6MWD (P = 0.005), NHYA-FC III-IV (P = 0.0001), TAPSE/sPAP ratio ≤0.20 (P = 0.017), PVR (P = 0.008), and TAPSE/sPAP ratio ≤0.20 combined with NYHA-FC III-IV (P = 0.0001) were significant determinants and TAPSE/sPAP ratio ≤0.20 combined with NYHA-FC III-IV was the only independent predictor of mortality (P = 0.003).Medically treated CTEPH patients with a TAPSE/sPAP ratio ≤0.20 had lower survival rates. TAPSE/sPAP ratio≤0.20 combined with NYHA-FC III-IV was the independent predictor of poor prognosis.CONCLUSIONMedically treated CTEPH patients with a TAPSE/sPAP ratio ≤0.20 had lower survival rates. TAPSE/sPAP ratio≤0.20 combined with NYHA-FC III-IV was the independent predictor of poor prognosis.